2002
DOI: 10.1073/pnas.132556899
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism of action of theophylline: Induction of histone deacetylase activity to decrease inflammatory gene expression

Abstract: The molecular mechanism for the anti-inflammatory action of theophylline is currently unknown, but low-dose theophylline is an effective add-on therapy to corticosteroids in controlling asthma. Corticosteroids act, at least in part, by recruitment of histone deacetylases (HDACs) to the site of active inflammatory gene transcription. They thereby inhibit the acetylation of core histones that is necessary for inflammatory gene transcription. We show both in vitro and in vivo that low-dose theophylline enhances H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
326
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 458 publications
(338 citation statements)
references
References 28 publications
8
326
0
4
Order By: Relevance
“…Accumulating evidence indicates that at lower doses, theophylline has anti-inflammatory effects, but these are probably not mediated by phosphodiesterase inhibition because the inhibition of these enzymes is trivial at low plasma concentrations that are clinically effective (49). We have recently shown that the anti-inflammatory effects of theophylline may be mediated via activation of HDAC and that this effect is independent of phosphodiesterase inhibition (50). Low doses of theophylline significantly increase HDAC activity in bronchial biopsy specimens from asthmatic patients, and the increase in HDAC activity is correlated with the reduction in airway eosinophils (50).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidence indicates that at lower doses, theophylline has anti-inflammatory effects, but these are probably not mediated by phosphodiesterase inhibition because the inhibition of these enzymes is trivial at low plasma concentrations that are clinically effective (49). We have recently shown that the anti-inflammatory effects of theophylline may be mediated via activation of HDAC and that this effect is independent of phosphodiesterase inhibition (50). Low doses of theophylline significantly increase HDAC activity in bronchial biopsy specimens from asthmatic patients, and the increase in HDAC activity is correlated with the reduction in airway eosinophils (50).…”
Section: Reviewmentioning
confidence: 99%
“…We have recently shown that the anti-inflammatory effects of theophylline may be mediated via activation of HDAC and that this effect is independent of phosphodiesterase inhibition (50). Low doses of theophylline significantly increase HDAC activity in bronchial biopsy specimens from asthmatic patients, and the increase in HDAC activity is correlated with the reduction in airway eosinophils (50). Because corticosteroids also activate HDAC, but via a different mechanism, theophylline should enhance the anti-inflammatory actions of corticosteroids; this enhancement occurs because the HDAC recruited to the inflammatory gene will be more effective at switching off the gene.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Substituted xanthine derivatives are a class of biologically active substances that are well-defined and widely studied in terms of their pharmacological activity as adenosine receptor antagonists, phosphodiesterase inhibitors, and inducers of histone deacetylase activity (Kalla et al, 2006;Lin et al, 2006;Ito et al, 2002). Due to these and several other known factors, this group have become broadly used in medicine not only as agents affecting the central nervous system, but also as active substances in the field of asthma, bronchitis, and chronic obstructive pulmonary diseases and as diuretics, cardiac stimulants, and renal protective agents (Caramori et al, 2003;Dal Piaz & Giavannoni, 2000;Kiesman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%